THE INFLUENCE OF ASN BERAKHLAK CORE VALUES ON EMPLOYEE PERFORMANCE AT THE POPULATION AND CIVIL REGISTRATION SERVICE OF SERANG CITY - Vedyra Jotha, Tinka; Widyastuti, Yeni (Prodi Administrasi Publik FISIP UNPAS, 2025)
The State Civil Apparatus has an important role in carrying out public service activities, both in government agencies or institutions in which there is a work culture that is adopted and implemented by ASN as actors in public organizations. To realize the work culture of the state civil apparatus as expected, it is necessary to strengthen the work culture of the state civil apparatus regularly and in a structured manner. For this reason, the Circular of the Minister of PANRB Number 20 of 2021 concerning the Implementation of Core Values and Employer Branding of the State Civil Apparatus was issued, in order to strengthen the work culture as one of the strategies for transforming ASN management towards a world-class government for the uniformity of the basic values of ASN that must be upheld by all ASN, namely the core values of ASN BerAKHLAK. The purpose of this study is to determine how much influence the core values of ASN BerAKHLAK have on employee performance at the Population and Civil Registration Service of Serang City. The research method used in this study is the associative research method using a quantitative approach. The population in this study were State Civil Apparatus working at the Population and Civil Registration Service of Serang City with a sample size of 27 people. The sampling technique used the Saturated Sampling technique. The results of this study indicate that there is a significant influence between the core values of ASN BerAKHLAK on employee performance with a magnitude of influence reaching 73.1% and the remaining 26.9% is estimated to be influenced by other factors. The suggestions in this study are to improve the understanding and implementation of the core values of ASN BerAKHLAK, and focus on improving the quality of service to the community, as well as providing training for employee competency development. Keywords : Core Values, ASN Ber-AKHLAK, Employee